Garage and Curbside Parking Competition with Search Congestion - Eren Inci; Robin Lindsey (European Regional Science Association (ERSA), 2014)
In many downtown areas, privately operated parking garages compete with each other and with publicly operated curbside parking. Garages exercise market power by charging fees that vary with parking duration. Curbside space is scarce, and drivers have to search for it. This creates a congestion externality and enhances garages' market power. We show that with inelastic parking demand setting differentiated hourly curbside parking fees can support the social optimum without regulating garage fees. Second-best uniform curbside fees can also perform well. In general, first-best and second-best parking fees are sensitive to parking supply and demand conditions, and therefore should be tailored to local circumstances.
Keywords: D62; L13; R41; R48; 330; endogenous outside option; parking; price discrimination; search costs; spatial competition